(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Cardiovascular mortality accounts for a high percentage but is mainly due to atherosclerosis, in which dyslipidemia is a significant risk factor to cause. According to traditional medicine, the body constitution strongly influences diseases and is studied much in the world to support diagnosis and orientation of disease prevention, but currently Vietnam has not been studied much. Objectives: To analyze the correlation between the characteristics of the traditional medicine body constitution and the blood lipid indicator and some factors relating to people with dyslipidemia. Subjects and methods: Analytical cross-sectional study with an analysis of 398 patients over 18 years old and diagnosed with the primary dyslipidemia at the Hospital of Traditional Medicine in Ho Chi Minh City from Mar. 2022 to Sep. 2022. Results: Out of the body constitutions, the phlegm dampness constitution accounted for the highest percentage (26.4%). Conclusion: There is a correlation between body constitutions and dyslipidemia, traditional medicine body constitution (p < 0.001). The phlegm dampness constitution and LDL - C, and HDL - C index are correlated with each other (p < 0.05).